Long-term survival outcomes of HIV infected children receiving antiretroviral therapy: an observational study from Zambia (2003–2015) - Jane N. Mutanga; Simon Mutembo; Amara E. Ezeamama; Xiao Song; Robert C. Fubisha; Kunda Mutesu-Kapembwa; Derrick Sialondwe; Brenda Simuchembu; Jelita Chinyonga; Philip E. Thuma; Christopher C. Whalen (BMC Public Health, 2019)
Abstract Background In 2017, 64% of children living with HIV in Zambia accessed Antiretroviral Therapy (ART). Despite expanded ART coverage, there is paucity of information on effectiveness of pediatric ART in reducing mortality. The aim of this research is to describe treatment outcomes, measure mortality rates and assess predictors of mortality among children receiving ART. Methods Using a retrospective cohort study design, we abstracted routinely collected clinical data from medical records of children from birth to 15 years old, who had received ART for at least 6 months at Livingstone Central Hospital in Southern Province Zambia, between January 2003 and June 2015. The primary outcome was death. Cause of death was ascertained from medical records and death certificates. Distribution of survival times according to baseline covariates were estimated using Kaplan Meier and Cox Proportional Hazards methods. Results Overall, 1039 children were commenced on ART during the study period. The median age at treatment initiation was 3.6 years (IQR: 1.3–8.6) and 520 (50%) children were female. Of these, 71 (7%) died, 164 (16%) were lost to follow-up, 210 (20%) transferred and 594 (56%) were actively on treatment. After 4450 person years, mortality rate was 1.6/100 (95% CI: 1.4–1.8). Mortality was highest during the first 3 months of treatment (11.7/100 (95% CI: 7.6–16.3). In multivariable proportional hazards regression, the adjusted hazards of death were highest among children aged < 1 year (aHR = 3.1 (95% CI: 1.3–6.4), compared to those aged 6–15 years, WHO stage 4 (aHR =4.8 (95% CI: 2.3–10), compared to WHO stage 1 and 2. In the sensitivity analysis to address bias due to loss to follow-up, mortality increased 5 times when we assumed that all the children who were lost to follow up died within 90 days of their last visit. Conclusion We observed low attrition due to mortality among children on ART. Loss to follow-up was high (16%). Mortality was highest during the first 3 months of treatment. Children aged less than one year and those with advanced WHO disease stage had higher mortality. We recommend effective interventions to improve retention in care and early diagnosis of HIV in children.